LOW VITAMIN B12 DIET INCREASES LIVER HOMOCYSTEINE LEVELS AND LEADS TO LIVER STEATOSIS IN RATS - Sianipar, Imelda Rosalyn; Ujianti, Irena; Yolanda, Sophie; Jusuf, Ahmad Aulia; Kartinah, Neng Tine; Amani, Patwa; Murti, Krishna Aditya; Soeria Santoso, Dewi Irawati (Universa Medicina, 2019)
Background Nonalcoholic fatty liver disease (NAFLD) is one of the most widespread chronic liver diseases, caused by the development of insulin resistance. One of the mechanisms involved is a disturbance in insulin signaling by certain toxic substances that interact with one of the proteins responsible for the insulin signaling pathway. Increased homocysteine level, upon disruption of the methionine pathway, is associated with insulin resistance. The aim of this study was to evaluate the effect of hyperhomocysteinemia and insulin resistance (HOMA-IR level) induced by dietary vitamin B12 restriction on liver steatosis. Methods A study of laboratory experimental design was conducted involving 18 male Sprague Dawley rats (age 36-40 weeks, BW 300-350 g), that were randomly divided into 3 groups: control, 8-week treatment, and 16-week treatment. Standard AIN-93 diet was administered to the control group, whereas rats in the treatment groups were fed vitamin B12 deficiency-AIN-93M. At the end of treatment, liver homocysteine levels were determined by ELISA, HOMA-IR values were calculated, and steatosis degree of the liver was determined histologically. Statistical analysis was performed using independent t-test. Results A significant increase in liver homocysteine levels was found between the control and both the 8- and 16-week treatment groups (p<0.001). HOMA-IR levels were significantly higher in both treatment groups compared to controls (p<0.001). The area of liver steatosis in both treatment groups was significantly larger than that of the control group (p<0.001). Conclusion Increased homocysteine levels due to dietary vitamin B12 deficiency induces liver steatosis due to insulin resistance in rats.